Identification of coordination factors affecting building projects performance - Alaloul, W.S. (Elsevier B.V., 2016)
Construction projects performance requires improvement to fulfil the complexity of the stakeholdersâ needs and expectations. Coordination process is proposed as an efficient solution for weak performance of construction projects. Therefore, coordination factors are vital in ensuring a successful implementation of all project phases. This study aimed to identify and prioritise coordination factors that influence the performance of building projects in Malaysian context. A vast body of literature on coordination process was reviewed and resulted in 53 coordination factor. Three rounds of Delphi technique were conducted. The most effective coordination factors were ranked based on the Relative Importance Index (RII) such as Scheduling (RII = 0.97), Quality assurance plan (RII = 0.93), and all partiesâ participation in plans (RII = 0.89). These coordination factors have fulfilled the research gap and provided better management and higher performance for project parties. The results offer insightful perspectives to define the most effective coordination factors, for addressing the dependency between project tasks and the parties to enhance project performance. Â© 2016 Faculty of Engineering, Alexandria University